2017
DOI: 10.1097/pcc.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Improved Clinical Performance and Teamwork of Pediatric Interprofessional Resuscitation Teams With a Simulation-Based Educational Intervention*

Abstract: Participation in a simulation-based team training educational intervention significantly improved surrogate measures of clinical performance, time to initiation of key clinical tasks, and teamwork during simulated pediatric resuscitation. A positive correlation between clinical and teamwork performance suggests that effective teamwork improves clinical performance of resuscitation teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 34 publications
6
65
1
1
Order By: Relevance
“…22,23 Many of the studies on the pediatric literature focus on the use of simulation to teach skills related to resuscitation algorithms (PALS and neonatal resuscitation program), with teamwork skills often being a secondary learning objective with effectiveness of interventions based on self-assessment questionarries. 15,22,23 In contrast to studies that apply a mixed methodological approach to teamwork training through theoretical lectures, video analysis, and role-playing, 1,3 we demonstrated that SBTT training alone impacts bedside performance during real emergency events.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…22,23 Many of the studies on the pediatric literature focus on the use of simulation to teach skills related to resuscitation algorithms (PALS and neonatal resuscitation program), with teamwork skills often being a secondary learning objective with effectiveness of interventions based on self-assessment questionarries. 15,22,23 In contrast to studies that apply a mixed methodological approach to teamwork training through theoretical lectures, video analysis, and role-playing, 1,3 we demonstrated that SBTT training alone impacts bedside performance during real emergency events.…”
Section: Discussioncontrasting
confidence: 59%
“…Performing a needs assessment through the collection of preintervention real-time data through event analysis allowed us to identify granular details and characteristics that were impacting team performance effectiveness. Unlike pediatric studies by Gilfoyle et al 15 that applied a two-stage Delphi process to develop training content, we used assessment of real clinical events specific to our ICU to create our training program. Ability to identify specific deficiencies such as team leader confusion, lack of role clarity, and ineffective communication, gleaned from teamwork scores and staff commentary, provided granular details key to establishing SBTT objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating teamwork principles in the PICU, pediatric emergency department, and in simulated pediatric resuscitation exercises improved knowledge, attitudes, confidence, and team performance (Bultas, Hassler, Ercole, & Rea, 2014;Messmer, 2008;Patterson, Geis, LeMaster, & Wears, 2013;Thomas et al, 2007;Weinstock et al, 2005). Similar results occurred with simulation training and teams assembled for emergency care in other clinical venues (Gilfoyle et al, 2017;Reynolds, Ayres-de-Campos, & Lobo, 2011). Team recognition and performance in the management of clinical deterioration in acute care pediatric settings requires additional study.…”
Section: Social Interaction With Physicians and Parentsmentioning
confidence: 82%
“…When working to decrease inefficiency in the OR, health care leaders often focus on methods to increase the technical skills of the surgeon or the individual clinician, even when poor teamwork can contribute more prominently to negative patient surgical outcomes . Leaders can encourage collaboration and close working relationships through team‐building exercises such as the TeamSTEPPS program, through simulation‐based training, and by fostering a work environment that encourages engagement of staff members …”
Section: Discussionmentioning
confidence: 99%